Il riuso degli edifici di culto: profili problematici tra diritto canonico, civile e amministrativo (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Introduzione - 2. Problematiche di diritto canonico: la gravità della causa e l’uso non indecoroso tra normativa e giurisprudenza - 3. Problematiche tra diritto civile e diritto canonico: il vincolo di destinazione al culto - 4. Problematiche di diritto civile: la scelta dello strumento giuridico - 5. Problematiche di diritto amministrativo: il divieto di distruzione e di uso illecito e il cambiamento di destinazione d’uso compatibile con il carattere storico e artistico dell’edificio - 6. The future of churches: casi di studio e riflessioni a partire dal convegno di Bologna - 7. Conclusioni.The reuse of places of worship: problematic aspects between canon law, civil law and administrative lawAbstract: This article focuses on the juridical problematic aspects linked to the reuse of places of worship. It wants to examine the notion of “other grave causes” and “not sordid use” in canon law, the hypothecation as a place of worship and the choice of the more appropriate juridical instrument in the Italian civil law and the application of the Italian cultural heritage code, with the prohibition of destroying and of illegal use and the communication of the change in use, in administrative law. In conclusion, it is proposed a brief reference to the case studies and reflections from The future of churches, a conference that took place in Bologna, from 5th to 7th October 2016, and that was organized by the Department of Architecture at the University of Bologna and the Centro Studi Cherubino Ghirardacci.
Keywords: Edifici ed edilizia di culto